Pushing boundaries—culture‐sensitive care in oncology and palliative care: a qualitative study. Issue 6 (12th August 2016) - Schrank, Beate; Rumpold, Tamara; Amering, Michaela; Masel, Eva Katharina; Watzke, Herbert; Schur, Sophie
Abstract: Objective: In increasingly globalized societies, patient‐centered cancer care requires culture‐sensitive approaches in order to ensure patients well‐being. While migrant patients' needs are frequently reported in the literature, staff members' perception of work with migrant patients, associated challenges, or individual work approaches are largely unknown. This study addresses this research gap through qualitative exploration of experiences of multicultural health care professionals in supportive oncology and palliative care, working with patients from different cultural backgrounds. This study aims to understand staff experience of the impact of culture on cancer care. Methods: This study was conducted at the Medical University of Vienna, including staff from different settings of oncology and palliative care, in different professional positions, and with a range of individual migration backgrounds. Semistructured interviews were conducted with 21 staff members working with patients from different cultural backgrounds. Interviews explored views on the impact of culture on care were audio‐taped, transcribed, and analyzed using a rigorous method of thematic analysis, enhanced with grounded theory techniques. Results: Interviews revealed 4 key topics: culture‐specific differences, assumed reasons for differences, consequences of multicultural care, and tools for culture‐sensitive care. Strategies to better deal with migrant patients and their families were suggested to improve work satisfaction amongst staff. Conclusions: This study identifies relevant staff challenges in work with migrant patients. Concrete suggestions for improvement include measures on an organizational level, team level, and personal tools. The suggested measures are applicable to improve work satisfaction and culture‐sensitive care not only in cancer care but also in other areas of medicine.